KETERLIBATAN MASYARAKAT TERHADAP PENCEMARAN PERAIRAN PESISIR KOTA PALOPO: Indonesia - Rahmita Rahmita; Hasrianti; Dahniar; Auliya Citra (Jurnal Biogenerasi, 2023)
The amount of population pressure in coastal areas is one of the factors causing damage to the aquatic environment. Damage to the coastal environment is dominated by oil pollution, mangrove damage, coastal abrasion and waste. This phenomenon indicates that communities activity is a major cause of damage to the coastal environment. This research aims to study the implication of communities in terms of knowledge, attitudes and behavior of coastal communities against coastal water pollution. The method used of survey, documentation, and interview to the coastal communities in Palopo with a questionnaire. The data questionnaire analysis was carried out descriptively. The results of the analysis of the questionnaire data show that the low percentage of the level of knowledge of coastal communities about management rules and the importance of protecting the environment influences the attitudes and behavior of the people who tend to dispose of waste into the aquatic environment.